Hollow-Core Optical Fibers for Telecommunications and Data Transmission - Krzysztof Borzycki; Tomasz Osuch (Applied Sciences, 2023)
Hollow-core optical fibers (HCFs) have unique properties like low latency, negligible optical nonlinearity, wide low-loss spectrum, up to 2100 nm, the ability to carry high power, and potentially lower loss then solid-core single-mode fibers (SMFs). These features make them very promising for communication networks and similar applications. However, this class of fibers is still in development. Current applications are almost exclusively limited to low-latency data links for High-Speed Trading (HST); other uses are in the trial stage now. In this paper, we comprehensively review the progress in the development of HCFs including fiber design, fabrication and parameters (with comparisons to conventional single-mode fibers) and support technologies like splicing and testing. A variety of HCF applications in future telecom networks and systems is analyzed, pointing out their strengths and limitations. Additionally, we review the influence of filler gas and entry of contaminants on HCF attenuation, and propose a new fusion splicing technique, avoiding the destruction of the fiber’s photonic cladding at high temperature.